2018
DOI: 10.4236/ojn.2018.85026
|View full text |Cite
|
Sign up to set email alerts
|

Development of Conceptual Framework from the View of Patients and Professionals on Patient Engagement: A Qualitative Study in Hong Kong SAR, China

Abstract: Objective: To investigate patient engagement to gain understandings of professional and patient's views and inform the development of a patient engagement conceptual framework for further development of a valid and reliable evaluated measure. Method: 17 selected hospitals from Hong Kong East Cluster, Hong Kong West Cluster, Kowloon Central Cluster, Kowloon East Cluster and New Territory East Cluster of Hospital Authority Hong Kong involved in the study. Focus groups were conducted with 37 medical staffs, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…Patient SSDM was assessed using a self-administered questionnaire. It was developed based on our previous patient engagement framework [ 36 ] and index [ 37 ], findings from literature review, focus group interviews (including patients, doctors, nurses, and policy makers), and expert discussion. It assessed patient satisfaction with decision-making, along with doctors in clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…Patient SSDM was assessed using a self-administered questionnaire. It was developed based on our previous patient engagement framework [ 36 ] and index [ 37 ], findings from literature review, focus group interviews (including patients, doctors, nurses, and policy makers), and expert discussion. It assessed patient satisfaction with decision-making, along with doctors in clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…The original framework was established based on literature reviews and a series of previous focus group interviews of both professionals and patients in the local health care system. 25 The modified framework suggested that patient engagement should be a relationship, which is reciprocal, dynamic, and pluralistic, rather than an invariable status among patients, professionals, and the organizations. The framework presented five levels of patient engagement (self-information search, enquiry, bidirectional communication, discussion, and partnership).…”
Section: Methodsmentioning
confidence: 99%
“…Kuesioner pelibatan pasien digunakan untuk mengukur pelibatan pasien dalam asuhan keperawatan di masa pandemi Covid-19. Kuesioner pelibatan pasien dalam asuhan keperawatan yang digunakan dalam penelitian ini merupakan kuisioner yang dimodifikasi dari kuesioner d Patient Engagement Index (Xu et al, 2018), The Conceptual Framework of Patient Engagement (Wong et al, 2018)…”
Section: Kuesioner Pelibatan Pasienunclassified
“…Pemberian informasi tentang semua aspek asuhan medis dan tindakan, termasuk asuhan dan tindakan keperawatan juga sudah diatur dalam Standar HPK 2.1 dalam SNARS (2019). Pemberian informasi dan edukasi pada pasien yang dilakukan dalam asuhan keperawatan menurut Wong et al (2018), juga meliputi informasi dan edukasi dari pasien masuk hingga pasien pulang.…”
Section: Gambaran Pelibatan Pasien Dalam Asuhan Keperawatan DI Masa P...unclassified
See 1 more Smart Citation